Exact algorithms for multiobjective linear optimization problems with integer variables: A state of the art survey - Pascal Halffmann; Luca E. Schäfer; Kerstin Dächert; Kathrin Klamroth; Stefan Ruzika (Journal of Multi-Criteria Decision Analysis, 2022)
We provide a comprehensive overview of the literature of algorithmic approaches for multiobjective mixed-integer and integer linear optimization problems. More precisely, we categorize and display exact methods for multiobjective linear problems with integer variables for computing the entire set of nondominated images. Our review lists 108 articles and is intended to serve as a reference for all researchers who are familiar with basic concepts of multiobjective optimization and who have an interest in getting a thorough view on the state-of-the-art in multiobjective mixed-integer programming.
Keywords: 300; algorithms; integer; literature overview; mixed-integer; multiobjective optimization